Menyuarakan Iman di Tengah Penindasan: Analisis Naratif Tematik Kisah Gadis Tawanan dari 2 Raja-Raja 5:1-5 - Aska Aprilano Pattinaja (Sekolah Tinggi Teologi Nusantara, 2025)
This captive girl demonstrated an active faith in spite of her oppression. Her testimony became the catalyst for Naaman's healing and his encounter with the God of Israel. This study aims to explore the narrative and thematic dynamics of the story, especially in relation to the themes of witness, God's providence, and inclusiveness in the plan of salvation. This study uses narrative and thematic analysis methods to uncover the theological messages contained in the actions and words of the captive girl. Therefore, four important values emerge from this research: first, the power of forgiveness; second, being trustworthy; third, having mercy; and fourth, trusting God. This research enriches biblical theology's understanding of the role of the